The effect of material parameters on chip formation in orthogonal cutting simulation of Ti-5553 Alloy - KAYNAK, YUSUF (ELSEVIER SCIENCE BV, 2017)
It is a well-known fact that Titanium alloys are commonly used materials in various industries, in particular aerospace and biomedical applications. Among titanium alloys, Ti-5553 is a new generation high temperature near beta alloy. As it has superior properties such as high tensile strength and fatigue life, it has a potential to be used in aerospace industries for structural components to replace Ti-6Al-4V. This study provides investigation on the effect of material parameters including material model parameters and frictional conditions on simulating chip formation in orthogonal cutting process of this alloy. Experimental data are used to compare forces, contact length, and to predict chip form in the cutting process of Ti-5553 alloy. This study illustrates that with calibrated frictional condition and critical damage value, it is possible to predict forces, contact length and chip morphology that can show good agreement with experimental data. (C) 2017 The Authors. Published by Elsevier B.V.
Keywords: Finite Element Simulation; Ti-5553 Alloy; Orthogonal Cutting; MACHINABILITY; TI-6AL-4V; SPEED